Microsatellite data analysis for conservation of two goat breeds - TANTIA, M S; BEHL, RAHUL; SHEORAN, NBELAM; SINGH, RITI; VIJH, R K (The Indian Journal of Animal Sciences, 2014)
Microsatellite data on 22 loci were generated for Black Bengal and Chegu breeds of goats and subjected to statistical analysis to test whether the populations had undergone recent genetic bottleneck. All the three models of microsatellite evolution were utilized for the purpose. The principle behind the three tests to check for the heterozygosity excess was that there is transient increase in the hetetbzygosity with a reduction in allelic diversity. Both the populations were found to have undergone genetic bottleneck using IAM, TPM and SMM in parametric statistical tests. The graphical test did not reveal any distortion of allelic frequency distribution and both populations exhibited the normal L shaped curve. The Black Bengal goat has large population but the effective population size. (Ne) needs to be increased for sustainability of diversity. In Chegu goats, which have limited population, measures are warranted to increase Ne by introduction of planned breeding programmes.